Restrained eating and self-esteem in premenopausal and postmenopausal women - Drobnjak, Susana; Atsiz, Semra; Ditzen, Beate; Tuschen-Caffier, Brunna; Ehlert, Ulrike (Journal of eating disorders, 2014)
There has been limited research about disordered eating in middle-aged women, and to date, few data exist about restrained eating behavior in postmenopausal women. Therefore, the aim of this study was to examine eating behavior with a specific focus on menopause as an associated factor in restrained eating. Beyond this, we were interested in how postmenopausal status and self-esteem would interact to determine eating patterns in women in middle age.
Gesehen am 10.02.2021